2018
DOI: 10.3390/ijms19113497
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Proteins Expressed between Human and Mouse Adipose-Derived Mesenchymal Stem Cells by a Proteome Analysis through Liquid Chromatography with Tandem Mass Spectrometry

Abstract: Adipose-derived mesenchymal stem cells (ADSCs) have become a common cell source for cell transplantation therapy. Clinical studies have used ADSCs to develop treatments for tissue fibrosis, such as liver cirrhosis and pulmonary fibroma. The need to examine and compare basic research data using clinical research data derived from mice and humans is expected to increase in the future. Here, to better characterize the cells, the protein components expressed by human ADSCs used for treatment, and mouse ADSCs used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Indeed, a recent proteomic study showed that 92% of proteins in adipose-derived mesenchymal stem cells of mouse and human are consistent. 60 We also added minimal details to the interactions of Met and α5β1 to be able to study the effect of AXT050 that targets and breaks the interaction of α5β1 with Met. HGF-independent activation of Met from binding of α5β1 to fibronectin 22 was neglected in this model due to lack of sufficient experimental data, but could be implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent proteomic study showed that 92% of proteins in adipose-derived mesenchymal stem cells of mouse and human are consistent. 60 We also added minimal details to the interactions of Met and α5β1 to be able to study the effect of AXT050 that targets and breaks the interaction of α5β1 with Met. HGF-independent activation of Met from binding of α5β1 to fibronectin 22 was neglected in this model due to lack of sufficient experimental data, but could be implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β1 expression is important for mice MSCs migration, while C-X-C chemokine receptor type 4 expression is involved for human MSC migration to sites of tissue injury[ 24 - 25 ]. It has been demonstrated that 92% of MSC protein expression is similar in humans and mice[ 26 ]. MSCs represent only a small proportion of the cells in bone marrow, and their proliferation and differentiation capacity correlates inversely with age[ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have analyzed the contents of extracellular vesicles released by adipose tissue-derived MSCs [8,46]. Others have performed secretome analysis with low-resolution techniques, which has not provided exhaustive information [47,48].…”
Section: Discussionmentioning
confidence: 99%